PENILAIAN KINERJA TRANSPORTER PRODUK TIANG LISTRIK MENGGUNAKAN SUPPLY CHAIN OPERATIONS REFERENCE PADA PT. BPI - Swara Hardawina, Ardhya Gemuruh; Nurhasanah, Nunung (Jurnal Ilmiah Teknik dan Manajemen Industri, 2024)
PT. BPI is a manufacturing company specializing in steel pipes, electric poles, and similar products, located in Bekasi. In its supply chain operations, the company utilizes transporter services for product delivery. However, delays in delivery have occurred, affecting the achievement of targets, thus requiring an evaluation of transporter performance. This research aims to evaluate supply chain performance, identify problematic indicators, and propose improvements. The performance measurement is conducted using the Supply Chain Operations Reference (SCOR) method, which covers the entire supply chain process from upstream to downstream. The data used for the measurement were provided by the company and analyzed based on relevant performance attributes and metrics. Additionally, the weighting of each metric is done using the Analytic Hierarchy Process (AHP). The results show that the total performance matrix scores for the transporters are 98.254% for PT. BSM, 98.094% for PT. BGR, and 97.648% for PT. BARUNA, all falling under the "Excellent" performance category. However, several performance indicators fall under the "average" and "marginal" categories, which require priority improvements. These improvements are proposed based on best practices from the SCOR method.